PERCEPTIONS OF THE USE OF WEB 2.0 TOOLS IN SECOND LANGUAGE COLLABORATIVE WRITING - PÉREZ-AMARO, Elsa Guadalupe (Revista Internacional de Ciencias Sociales y Humanidades SOCIOTAM, 2021)
This article presents a survey data of university students enrolled in a course in applied linguistics on the use of web tools in the collaborative writing process. This study is derived from a larger one that analyzes tools such as Facebook, wikis, and blogs within the writing process in a second language. The goal of this study was to determine students´ perceptions of the different tools in an academic setting, the skill level, and collaboration. The theoretical framework is based on the social theory of learning and communities of practice.